An Analysis of Figurative Languages on Teressa Teng’s Song Lyrics - Risca Chairiah Tanjung; Rudiansyah Rudiansyah; Julina Julina (Published by Confucius Institute UNS, 2022)
This research was entitled “An Analysis of Figurative languages on Teressa Teng’s Song Lyrics”. Teressa Teng was a singer from Taiwan who was highly admired in Taiwan and China. During her lifetime, Teresa had popular songs, including 甜蜜蜜 (tián mìmì), 月亮代表我的心 (yuèliàng dàibiǎo wǒ de xīn), 梅花 (méihuā), 你怎么说 (nǐ zěnme shuō), 爱人 (àirén), 我只在乎你 (wǒ zhǐ zàihū nǐ), 小城故事 (xiǎochéng gùshì), 偿还 (chánghuán)，再见我的爱人 (zàijiàn wǒ de àirén), and 千言万语 (qiānyán wàn yǔ). These songs were very popular cross-year songs. Therefore, these songs were analyzed in this research. This research objective was to describe some figurative languages in the lyrics of Teressa Teng’s songs by utilizing stylistic theory and contextual semantics. The research method was a qualitative descriptive method. The research data were the lyrics of Teressa Teng’s songs. The data sources of this research were ten songs by Teressa Teng. Based on the research results, there were ten types of figurative languages in the Teressa Teng’s song lyrics, namely: Kuāzhāng 夸张, Bǐyù 比喻, Fǎnfù 反复, Jǐngcè 警策, Bǐnǐ 比拟, Fǎnwèn 反 问, Fǎnyǔ 反语, Huíhuán 回环, Dǐngzhēn 顶真, and Tònggǎn 痛感.